Safety and walking ability of KAFO users with the C-Brace® Orthotronic Mobility System, a new microprocessor stance and swing control orthosis. (February 2017) - Pröbsting, Eva; Kannenberg, Andreas; Zacharias, Britta
Background: There are clear indications for benefits of stance control orthoses compared to locked knee ankle foot orthoses. However, stance control orthoses still have limited function compared with a sound human leg. Objectives: The aim of this study was to evaluate the potential benefits of a microprocessor stance and swing control orthosis compared to stance control orthoses and locked knee ankle foot orthoses in activities of daily living. Study design: Survey of lower limb orthosis users before and after fitting of a microprocessor stance and swing control orthosis. Methods: Thirteen patients with various lower limb pareses completed a baseline survey for their current orthotic device (locked knee ankle foot orthosis or stance control orthosis) and a follow-up for the microprocessor stance and swing control orthosis with the Orthosis Evaluation Questionnaire, a new self-reported outcome measure devised by modifying the Prosthesis Evaluation Questionnaire for use in lower limb orthotics and the Activities of Daily Living Questionnaire. Results: The Orthosis Evaluation Questionnaire results demonstrated significant improvements by microprocessor stance and swing control orthosis use in the total score and the domains of ambulation ( p  = .001), paretic limb health ( p  = .04), sounds ( p  = .02), and well-being ( p  = .01). Activities of Daily Living Questionnaire results showed significant improvements with the microprocessor stance and swing control orthosis with regard to perceived safety and difficulty of activities of daily living. Conclusion: The microprocessor stance and swing control orthosis may facilitate an easier, more physiological, and safer execution of many activities of daily living compared to traditional leg orthosis technologies. Clinical relevance: This study compared patient-reported outcomes of a microprocessor stance and swing control orthosis (C-Brace) to those with traditional knee ankle foot orthosis and stance control orthosis devices. The C-Brace offers new functions including controlled knee flexion during weight bearing and dynamic swing control, resulting in significant improvements in perceived orthotic mobility and safety.